تقييم درجة التلوث بعنصر الكادميوم وتحديد أهم أشكاله الكيميائية في تربة مكب البصة- محافظة اللاذقية - نيصافي, إبراهيم; الجبيلي, ريم (Latakia University Journal -Biological Sciences Series, 2018)
This research aimed to assess the degree contamination of soils in the Albassa dumpsite in Lattakia by Cadmium,and its mobility in the soil, The speciation of this element (distribution of a metal between different chemical form) have been performed using the method of digestion with aqua regia to estimate the total amount as well as the sodium hydroxide solution was used to extract the associated form with organic matter, while, the exchangeable form was extracted bymagnisium nitrate solution and the dissolved form was extracted by water. Eleven Soil samples were collected randomly from and around the dumpsite, on two depths (0-20 cm) and (20-40 cm),The results indicated that total amount of Cadmium were 12.6 mg/kg, above of the normal limits allowed in the agriculture lands, 1.5 mg/kg. The average amount of the associated form with organic matter reached 8.7mg/kg,where as the amount of exchangeable form was 6.1mg/kg and the dissolved one was 0.3mg/kg. The percentage of the associated form organic matter of the total amount was about 69 % while the percentage of the exchangeable form was 45 % and the percentage of dissolved form was 2 %. Thus, there is a risk of leaching Cadmium into the ground water and a possibility of absorption by the plants, especially that the studied soil was sandy textures in the addition of the strong mobility of Cadmium. يهدف هذا البحث إلى تقييم درجة تلوث ترب مكب البصة في محافظة اللاذقية بعنصر الكادميوم ودراسة حركيته من خلال تقدير كميته الكلية باستخدام طريقة الهضم بالماء الملكي لتقدير (المحتوى الكلي) ودراسة بعض أشكاله باستخدام محلول ماءات الصوديوم لتحديد كمية (الشكل المرتبط بالمادة العضوية) و (الشكل المتبادل) باستخدام محلول نترات المغنيزيوم و(الشكل المنحل) باستخدام الماء المقطر في تربة المكب المدروس. أخذت عينات التربة عشوائياً من أحد عشر موقعاً عشوائياً(داخل ووسط المكب ومحيطه) وذلك على عمقين: )0-20 سم) و)20-40 سم(.أشارت النتائج إلى أن متوسط الكمية الكلية لعنصرالكادميوم كانت 12.6مغ/كغ أي تجاوزت عتبة الحدود الطبيعية المسموح بها في الأراضي الزراعية وهي1.5 مغ/كغ, وكذلك كميته في ترب المكبات والبالغة 10 مغ/كغ). بلغ متوسط كميته المرتبطة بالمادة العضوية 8.7مغ/كغ, بينما كانت كمية الشكل المتبادل 6.1 مغ/كغ وبلغ متوسط كميته الذائبة (المنحل)0.3 مغ/كغ. وكذلك كانت القيم متقاربة في العمقين المدروسين, مما يشير إلى حدوث عمليات انغسال باتجاه الآفق السفلي. وسطياً بلغت النسبة المئوية للشكل المرتبط بالمادة العضوية حوالي 69%، بينما كانت النسبة المئوية للشكل المتبادل 45%والنسبة المئوية للشكل المنحل بالماء 2% من الكمية الكلية لهذا العنصر. تشير هذه النتائج إلى وجود إمكانية خطر انغسال العنصر المدروس ووصوله إلى المياه الجوفية أو امتصاصه من قبل النباتات لاسيما وأن التربة المدروسة رملية القوام عالية النفاذية. كما أثبتت هذه الدراسة وجود علاقات ارتباط طردية بين أشكال العناصر المدروسة وكذلك مع كميته الكلية وعدم وجود ارتباط مع قيم pH التربة نظراً لارتفاع قيمه وكذلك مع محتواها من المادة العضوية.